The Relationship Between Physical Activity and Blood Glucose Levels in Patients with Diabetes Mellitus at Narang Community Health Center - Simon, Maria Getrida; Nurhayati, Maria Afrasia; Natul, Fransiska Kurniati (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Diabetes mellitus (DM), commonly known as diabetes, is a serious chronic condition characterized by elevated blood glucose levels due to the body’s inability to produce or effectively use insulin. Physical activity refers to movements involving skeletal muscles that require more energy than resting, typically planned, continuous, and repetitive in nature, with the aim of improving physical fitness. The purpose of this study is to examine the relationship between physical activity and blood glucose levels in patients with diabetes mellitus. This study used a quantitative descriptive correlational approach with a cross-sectional design. The sampling technique was non-probability sampling, involving a total of 50 respondents. Data were analyzed using univariate and bivariate methods, specifically Kendall’s Tau B. The statistical analysis yielded a p-value of 0.000 (p < 0.05), indicating a significant relationship between physical activity and blood glucose levels among patients with diabetes mellitus at Narang Community Health Center. The findings indicate a positive correlation between physical activity and blood glucose levels in diabetic patients at Narang Community Health Center. Future researchers are encouraged to enhance the study design and broaden the sample selection. Additionally, attention should be given to unexplored factors that may influence blood glucose levels and were not communicated to respondents, in order to obtain more comprehensive results.